Experimental investigation on performance and emission characteristics of VCR engine working with biodiesel and Diethyl Ether. (2021) - Nishanth, S.; Gunasekar, N.; Nanthakumar, S.; Prakash, R.; Sampath Kumar, T.
Abstract: The increase in demand of fuel and number of populations using automobiles is at peak. We can see multinational companies making an effort to introduce electrical vehicles. Some experts believe that though electrical vehicles have several advantages it will be very difficult to compare with conventional internal combustion engine on performance and utility with E-vehicles. There is always a scope of innovation in the field of biofuels. Ordinary diesel can be mixed with biofuels in different propositions to attain better efficiency, thus by reducing diesel intake. The test was conducted with the identified chemicals like Jatropha Curcas, diethyl Ether with diesel at various propositions. The performance analysis of only diesel and biofuel mixed diesel were taken from VCR engine. The results indicated that a proposition in which Jatropha Curcas is in 25% proposition and diethyl Ether of 5% has the brake thermal efficiency increased by 6.32%, mechanical efficiency increased by 3.15% and the emission characteristics like HC, NOX emissions has reduced than Diesel. Thus, the results clearly show the increase in thermal properties of the fuel in which there is always scope for improvement.